Analysis of Design Elements on Secret Magic Control Agency Movie Poster - Bedjo Riyanto; Sarwono; Eli suryani (TAMA: Journal of Visual Arts, 2023)
In a film industry, advertising media is needed to promote or introduce films to be shown. One of the advertisements that is often used in cinema is posters. Posters are closely related to visual communication design, with visuals depicted can convey the important point of a film. Movie posters contain information and have design elements, namely visual elements and verbal elements contained in the design of Secret Magic Control Agency animated film posters. In the animated film, Secret Magic Control Agency is a family comedy film made in England and Russia based on popular fairy tales by brothers Gimm who are reliable storytellers who write many famous legendary fairy tales. The purpose of this study is to describe the elements of poster design and poster design styles used in Secret Magic Control Agency movie posters. The research method used is a qualitative descriptive method with data collection techniques, literature studies, and observations on Secret Magic Control Agency animated film posters. The design style of this poster is 3D, fun and secret agent adventure where the illustrations of the poster related to the magical world are depicted like real life objects that are colorful and contain fantasy which is very suitable for children. The Secret Magic Control Agency animated movie poster is made in accordance with the principles of layout, namely sequence and asymmetrical balance.